Metabolic resilience governs sex-specific pain recovery during hormonal aging: a multi-omics study of neuropathy in mice - Marinelli, Sara; Rossi, Claudia; Pieroni, Luisa; Giacovazzo, Giacomo; Vacca, Valentina; De Angelis, Federica; Cicalini, Ilaria; Mastrorilli, Valentina; Parisi, Chiara; Yurtsever, Zuleyha Nihan; Ciavardelli, Domenico; Coccurello, Roberto (Frontiers in Pain Research, 2025)
IntroductionBiological aging and sex interact to shape systemic metabolism, yet their role in chronic pain resolution remains unexplored. We hypothesized that metabolic resilience—the ability to flexibly switch fuel sources and maintain energy homeostasis—rules successful recovery from nerve injury in a sex-dependent manner during aging.MethodsIn 12-month-old male and female mice, corresponding to the perimenopausal phase in females and the onset of hormonal decline in both sexes, we induced sciatic nerve chronic constriction injury and performed multi-omics profiling during Wallerian degeneration, a phase known to trigger long-term neurobiological remodeling.ResultsAging females exhibited early activation of fatty acid oxidation, increased resting energy expenditure, upregulation of mitochondrial redox enzymes and circulating progesterone and corticosterone. Proteomic and metabolomic analysis revealed pentose phosphate pathway enrichment and gluconeogenesis, supporting redox balance and metabolic flexibility. Conversely, males displayed persistent glycolytic reliance, long-chain acylcarnitine accumulation, suppression of adiponectin and PPARγ, indicating metabolic inflexibility. Longitudinal behavioral analysis revealed that aging females recovered earlier and more fully than aging males, reversing the pattern previously shown in our adult mouse study, where females developed persistent pain and males recovered rapidly.DiscussionThese patterns highlight a non-linear, sex-specific interaction between biological aging and injury response, where hormonal decline reprograms the metabolic trajectory and reshapes pain outcomes. Metabolic resilience governs sex-specific recovery following nerve injury by directing early systemic adaptations that precede and predict long-term pain trajectories. These results define mechanistically anchored, sex- and age-specific biomarkers, and propose preclinical targets for timely, personalized interventions in age-associated neuropathic pain.